2012
DOI: 10.1088/1674-1056/21/5/057103
|View full text |Cite
|
Sign up to set email alerts
|

Ak·panalytical model for valence band of biaxial strained Ge on (001) Si1−xGex

Abstract: In this paper, the dispersion relationship is derived by using the k • p method with the help of the perturbation theory, and we obtain the analytical expression in connection with the deformation potential. The calculation of the valence band of the biaxial strained Ge/(001)Si 1−x Gex is then performed. The results show that the first valence band edge moves up as Ge fraction x decreases, while the second valence band edge moves down. The band structures in the strained Ge/ (001)Si 0.4 Ge 0.6 exhibit signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…[ 1–3 ] In such operations, it is highly desirable to achieve a tuneable response that could be obtained by applying independent external stimuli, such as pressure, humidity, temperature, or electrical/magnetic fields, to obtain reversible and dynamic information in real‐time. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] In such operations, it is highly desirable to achieve a tuneable response that could be obtained by applying independent external stimuli, such as pressure, humidity, temperature, or electrical/magnetic fields, to obtain reversible and dynamic information in real‐time. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors contribute to the failure of standard hybridization-based methods for the detection of 6mA in DNA. To surmount this challenge, several methods based on selective polymerase, 7 sensitive restriction enzymes 8 and the distinct stabilities between A/6mA–G base pairs 9 have been developed for the detection of 6mA in DNA. However, both the selectivity and sensitivity of some methods require further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…These data show an inverse linear relationship, suggesting that our strategy can be used in RNA m 6 A analysis. 15b , 27 …”
Section: Resultsmentioning
confidence: 99%
“…To circumvent the influence of secondary structures on primer hybridization and subsequent extension, we introduced simultaneous control primers (one adjacent to the probed site and the others with known methylation status). 15b , 27 Earlier studies have revealed two well-known m 6 A sites (position 1832 in 18S subunit and 4190 in 28S subunit) and two unmodified A residues (1781 in 18S subunit and 4189 in 28S subunit) in human rRNA. 28 In this study, fluorescently labeled primers with different lengths were designed such that their 3′ ends lie immediately adjacent to the target residue.…”
Section: Resultsmentioning
confidence: 99%